THE ROLE OF COMPUTER GRAPHICS IN TEACHING COMPUTER SCIENCE TO SCHOOL STUDENTS - Zaripov Nozimbek Nayimovich (International Engineering Journal For Research & Development, 2020)
The following article deals with computer graphics and their types; software packages that work with computer graphics, including graphic design, Corel DRAW vector graphics, Photo Shop raster graphics software, and Macromedia Flash software. The use of computer graphics software in teaching computer science helps students to increase their computer literacy, enhances their ability to work with the Internet, web design, and graphics, to develop their interest in computer graphics and to develop their knowledge, skills and abilities.